Knowledge of bioethics in health care workers in a tertiary care hospital - Trujillo-Vizuet, Ma Guadalupe; Sánchez-González, Roberto Alejandro; Gómez-Cruz, Omar; Domínguez-Arrevillaga, Sergio; Sepúlveda-Delgado, Jesús (Horizonte Sanitario, 2022)
Objective: Identify the level of knowledge about Bioethics in the health careworkers in a third level hospital, so that the bioethical dilemmas turn to theHospital Committee of Bioethics.Materials and Methods: A descriptive, cross-sectional and prospective studywas conducted. By means of a probabilistic sampling by strata, the sample sizewas calculated for a finite population n = 302 with a 95% confidence level, a visitto the areas was made in shifts, a questionnaire obtained from 2 questionnairesvalidated by Lynch et al., and Hernández et al. was applied. Within the ethicalconsiderations, a prior informed consent was applied to answer the questionnaire.A descriptive statistical analysis was performed.Results: The bioethical principles that the questionnaire reviews are autonomywhich was correctly identified in 17.2%, justice in 10.3%and charity in 14.6%.With respect to the level of knowledge, a 2% high knowledge, 33% regularknowledge, 33% knowledge low and 32% of null knowledge was found.Conclusions: Ethical dilemmas are presented every day, identifying properly byhealth care workers and channeling them to the Bioethics Hospital Committeewould be the ideal of every hospital that would allow us to properly contribute toa better decision -making in patient care.Keywords: Bioethics; health care workers; knowledge